Study of Potassium in Synovial Fluid as an Aid in Determining the Time Since Death (Indian Internet Journal of Forensic Medicine and Toxicology, 2019)
The estimation of the postmortem interval is one of the fundamental questions to be addressed at an autopsy examination. Accurate estimation of postmortem interval can be crucial to the successful investigation of a suspicious death. Knowing the postmortem interval can has investigators eliminate suspects if they have a valid alibi for when death occurred, allowing investigators to focus on other lands. Numerous studies have examined the potential utility of body fluids in estimating time of death. The purpose of this study was to establish correlation between postmortem interval and synovial potassium concentration and to derive a formula for determination of postmortem interval within reasonable time limit by putting synovial potassium concentration. Therefore in 50 cases with known time of death, synovial fluid was taken and analysed for potassium level on Beckman coulter autoanalyzer. Result shows linear rise of potassium consideration with increasing postmortem interval.
Keywords: Postmortem interval; Synovial fluid; Potassium; Time since death